Fate of carbon, nitrogen and phosphorus removal in a post-anoxic system treating low strength wastewater - SEMERCİ, NESLİHAN (ELSEVIER SCI LTD, 2016)
A lab-scale anaerobic-aerobic-anoxic sequencing batch reactor was operated for 135 days with using acetate as sole carbon source to explore the contribution of denitrifying phosphate accumulating organisms to nitrogen and phosphorus removal in a post-anoxic system. The system was operated at an aerobic sludge age of 2.5 days and DO level greater than 2 mg l(-1)under variable carbon to nitrogen (C/N) and carbon to phosphorus (C/P) ratios. More than 80% of influent nitrogen and phosphorus were removed simultaneously under aerobic conditions. When aerobic denitrification became limited due to the increase of average dissolved oxygen, overall nitrogen removal continued with the same efficiency, but with a larger contribution from anoxic denitrification. On the other hand, enhanced biological phosphorus removal activity decreased significantly as a result of free nitrous acid (FNA) inhibition. Fluorescence in situ hybridization analysis showed that the relative abundance of Actinobacter spp. was decreased by FNA inhibition while the relative abundance of Accumulibacter spp. remained unchanged. Conversely, the relative abundance of glycogen accumulating organisms (GAOs) increased from 7.1% to 23% as a result. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: EBPR; Phosphate accumulating organisms (PAOs); Glycogen accumulating organisms (GAOs); Denitrifying phosphorus removal; Post-anoxic; POLYPHOSPHATE-ACCUMULATING ORGANISMS; SEQUENCING BATCH REACTOR; BIOLOGICAL NUTRIENT REMOVAL; TREATMENT PLANTS; GRANULAR SLUDGE; SIMULTANEOUS NITRIFICATION; DENITRIFICATION; ACID; NITRITE; PERFORMANCE